Management of Kyphosis, Lumbar Spondylosis, and Mycobacterium avium Discitis in a 70-year Male with Chronic Lymphocytic Leukemia with Vascular Complication - Vadim Dolgov; David Frolov; Ryan Tapio; Samantha Hill; Miguel Schmitz (Journal of Orthopaedic Case Reports)
Introduction: Kyphosis is characterized by excessive forward curvature of the spine often causing back pain and stiffness, and occasionally, neurological deficit. Surgical management of kyphosis can entail an anterior lumbar interbody fusion (ALIF) in addition to a posterior spinal fusion with or without a laminectomy. Chronic lymphocytic leukemia (CLL) is a slow-growing cancer that affects the bone marrow. If ALIF is considered as a treatment option for kyphosis in a patient with CLL, attention needs to be taken to minimize complications. Case Report: A 70-year-old male with a history of kyphosis and CLL presented with refractory lower back pain attributed to his kyphosis. The patient required multiple procedures to correct his kyphosis including an ALIF between L3 and S1. During the ALIF, significant scar tissue and phlegmon were noted at the surgical site, and disc cultures revealed Mycobacterium avium. The accumulation of phlegmon and scar tissue required significant manipulation of the vessels to perform the procedure. Before closure of the anterior incision, the patient presented with absent pulses of the left leg. A thrombosis in the left iliac artery was noted and treated with stent placement during the surgery. Discussion: CLL leads to an immune compromised state which may lead to undiagnosed infections, specifically M. avium in our patient. Imaging showed the infection likely played a role in the disc degeneration of the lumbar spine, exacerbating the formation of the phlegmon and scar tissue. This required extensive manipulation of the vessels that resulted in the formation of thrombosis of the left iliac artery. Conclusion: Care must be taken during ALIF procedures on patients with CLL during manipulation of the vessels. If kyphosis is rapidly worsening in a patient with CLL, infection of the vertebra should be ruled out.